PHYTOCHEMICALS SCREENING AND ACTIVITIES OF BINAHONG (ANREDERA CORDIFOLIA [TEN.] STEENIS) LEAVES AND BEETROOTS (BETA VULGARIS L.) IN INCREASING SWIMMING ENDURANCE IN MICE - MASNIAH; JAMIDIN MANURUNG (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this research was to the identification of bioactive compounds and comparison of binahong (Anredera cordifolia [Ten.] Steenis) leaves and beetroots (Beta vulgaris L.) ethanol extract in swimming endurance activity in mice. Methods: The type of research that has been carried out is experimental laboratory which includes identification of bioactive content quality and testing of swimming endurance effect by comparing the difference between before and after treatment by binahong leaves and beetroots ethanol extract. Results: The results of bioactive compounds identification of binahong leaves and beetroots are alkaloids, glycosides, cyanogenic glycosides, flavonoids, and tannins. Steroid compounds are only found in binahong leaves. The results of swimming resistance are significantly different (p<0.05) in all groups. Animals group given 20% binahong leaves extract increased swimming resistance for 36,392 min, followed by caffeine for 33,440 minutes, then 10% binahong leaves extract for 29,142 min. Conclusion: Binahong leaves and beetroots have almost the same bioactive content except in the steroid content. The binahong leaves swimming endurance activity is higher than the bit bulbs.